THE TEACHERS’ STRATEGY OF IMPLEMENTING THE ONLINE LEARNING AT SMP NEGERI 2 TONDANO - Militika Chrisna Polii; Nihta Liando; Sanerita T. Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The aim of this research was to find out the teachers’ strategy of implementing the online learning. The method used in this research was descriptive qualitative and the technique sampling used in this research was semi-stucture interview, coding, and classifying. The researcher used semi structure interview to find the data by distributing questionnaire. The population of this research were 5 teachers at SMP N 2 Tondano. The results showed that the strategies used by the teacher to increase students' interest in learning were to provide students with 1) Self Preparation, 2) Preparing brief, clear, easy to understand, and interesting learning material, 3) Choosing a simple and attractive learning media, 4) Involving parents for helping teachers in online learning, 5) Conducting regular and continuous evaluations. Teaching and learning activities through online can work well when teachers, students and parents can work together and support each other.